Evaluating Service Quality Dimensions in Social Commerce: A Semi-Systematic Literature Review - Suwarno, Bukky; Dhewanto, Wawan; Belgiawan, Prawira Fajarindra (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
The widespread adoption of social media platforms has significantly transformed consumer behavior and business practices. This paper attempts to provide a detailed overview of extant research on service quality in social commerce, shedding light on the dimensions that influence customer satisfaction and engagement. By examining 26 research articles, this study identifies common dimensions of service quality and highlights gaps in the current studies, offering recommendations for future research. The findings of this review highlight responsiveness, security/privacy, reliability, and communication as the most frequent dimensions of service quality in social commerce. The outcomes of this study lead to the development of new service quality models in social commerce and provide valuable insights for both scholars and practitioners.